2006
DOI: 10.1097/01.ta.0000200075.12489.74
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced Acute Lung Injury is Attenuated by Phosphodiesterase Inhibition: Effects on Proinflammatory Mediators, Metalloproteinases, NF-??B, and ICAM-1 Expression

Abstract: Phosphodiesterase inhibition by PTX attenuates LPS-induced end-organ injury. In addition, proinflammatory cytokine production is also downregulated, likely because of the marked attenuation of NF-kappaB DNA binding and activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 66 publications
6
61
1
4
Order By: Relevance
“…In accordance, previous animal studies have demonstrated beneficial effects of PDE inhibitors in experimental ARDS by attenuating endotoxin-induced vasomotor dysfunction [17][18][19]. Besides influencing vasoreactivity, PDE inhibitors also have antiinflammatory properties, decreasing pulmonary edema, neutrophil infiltration, reactive oxygen species and levels of proinflammatory mediators in experimental acute lung injury [17][18][19]. These preclinical results suggest that inhibiting PDE may be a potential therapeutic target in ARDS.…”
Section: Introductionsupporting
confidence: 64%
“…In accordance, previous animal studies have demonstrated beneficial effects of PDE inhibitors in experimental ARDS by attenuating endotoxin-induced vasomotor dysfunction [17][18][19]. Besides influencing vasoreactivity, PDE inhibitors also have antiinflammatory properties, decreasing pulmonary edema, neutrophil infiltration, reactive oxygen species and levels of proinflammatory mediators in experimental acute lung injury [17][18][19]. These preclinical results suggest that inhibiting PDE may be a potential therapeutic target in ARDS.…”
Section: Introductionsupporting
confidence: 64%
“…There was no reduction of plasma MMP-9 and the authors did not comment on their reasons for omitting results for plasma MMP-2 levels. The authors analysed nuclear factor (NF)-kB activation using electrophoretic mobility shift assay and found increased activation in the LPS group, suggesting that these effects were mediated via NF-kB-dependent transcription of MMPs [48]. The lack of reduction in MMP-9 in this study may represent the release of stored MMP-9 from neutrophils in the treated group.…”
Section: Other Inhibitorsmentioning
confidence: 79%
“…In a rat model of i.v. LPS-induced lung injury, administration of 5 mg?kg -1 LPS via internal jugular vein caused histologically confirmed lung injury with increased levels of MMP-2 in BAL and MMP-9 in plasma at 4 h [48]. Coadministration of 25 mg?kg -1 PTX, a nonspecific phosphodiesterase inhibitor, reduced severity of lung injury and MMP-2 levels in BAL.…”
Section: Other Inhibitorsmentioning
confidence: 99%
“…However, other unexplored factors might have also accounted for the improved survival of newborn rats treated with PTX, including reduction in activation of nuclear factor-κβ and production of tumor necrosis factor-α, leading to attenuated lung injury (35), and the release of endothelium-derived nitric oxide by PTX in the pulmonary vascular bed, resulting in improved oxygenation (36). There are several potential limitations of this study.…”
Section: Ptx In Neonatal Hyperoxic Lung Injurymentioning
confidence: 88%